The Role of Technology in Modern TESOL Classrooms - Dilorom Poyonova; Sevara Abdishukurova; Makhliyo Shomurodova (Scientific Trends, 2025)
The integration of technology in Teaching English to Speakers of Other Languages (TESOL) has revolutionized language education. This article examines the impact of digital tools and artificial intelligence (AI) on TESOL methodologies, highlighting benefits, challenges, and future prospects.